(untitled) (Communications in Computational Physics, 2006)
A novel method for the generation of unstructured triangular surface meshes is presented. The method is based on remeshing techniques including edge splitting/contraction and edge swapping. Normalized edge lengths, based on a metric derived from curvature or from a user–specified spacing, are employed as the remeshing criterion. It is assumed that the geometry is input in the form of composite parametric surfaces, with Ferguson or Nurbs type multiple patch representation. Examples involving typical aircraft geometries and a ship model, are included to demonstrate how high quality meshes can be efficiently generated on surfaces with a high degree of geometric complexity.